Cycling cadence - Filliol, J.
About the question: What is the best cadence in cycling? Examining high performance cyclists and triathletes seems to confirm that cadences of 85-95 rpm are optimal for most athletes, and for most terrain. With proper training at these cadences (at all intensities), the higher cadences will be more economical and thus will result in faster times on the bike. And there is an added bonus: since higher cadences result in more glycogen being spared, especially in fast twitch fibres, there is the ability to have a faster sprint to the finish.